2016
DOI: 10.1007/s11010-015-2646-1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-D mediates fibrogenic response in myofibroblasts

Abstract: Vascular endothelial growth factor (VEGF)-D is a crucial mediator of angiogenesis. Following myocardial infarction (MI), cardiac VEGF-D and VEGF receptor (VEGFR)-3 are significantly upregulated. In addition to endothelial cells, myofibroblasts at the site of MI highly express VEGFR-3, implicating the involvement of VEGF-D in cardiac fibrogenesis that promotes repair and remodeling. The aim of the current study was to further explore the critical role of VEGF-D in fibrogenic response in myofibroblasts. Myofibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…VEGF-C and VEGF-D also serve as profibrogenic mediators that promote tissue fibrosis. 24,25 In this study, we observed significantly increased expression of VEGF-D ( Figure 3e) and VEGFR-3 ( Figure 3f) in the kidney of ALDO-treated rats. However, Ang1-7 co-treatment did not modify renal gene expression of VEGF-D and VEGFR-3 in ALDO-treated rats.…”
Section: Gene Expression Of Fibrotic Mediators In the Kidneysupporting
confidence: 60%
“…VEGF-C and VEGF-D also serve as profibrogenic mediators that promote tissue fibrosis. 24,25 In this study, we observed significantly increased expression of VEGF-D ( Figure 3e) and VEGFR-3 ( Figure 3f) in the kidney of ALDO-treated rats. However, Ang1-7 co-treatment did not modify renal gene expression of VEGF-D and VEGFR-3 in ALDO-treated rats.…”
Section: Gene Expression Of Fibrotic Mediators In the Kidneysupporting
confidence: 60%
“…Figf, also known as Vegfd, is a member of the platelet-derived growth factor/vascular endothelial growth factor (PDGF/VEGF) family and is important for angiogenesis, lymphangiogenesis, and EC growth. It also stimulates myofibroblast growth and collagen synthesis (121). Chrdl1 codes an antagonist of Bmp4.…”
Section: Discussionmentioning
confidence: 99%
“…A controlled apoptosis and a tidy epithelia-stroma interaction should occur at involved and uninvolved surrounding tissues 36,37 . Some recent evidence suggested that experimental inhibition of angiogenesis ameliorates the development of liver fibrosis, while other recent studies indicate that neutralization or genetic ablation of VEGF can delay tissue repair and fibrosis resolution in damaged tissues 38,39 . The imbalance between pro/anti-angiogenic mediators might contribute to apoptotic or sustain the process of fibrosis, as observed for CCN1/CYR61 involved in attenuating and/or scavenging of TGFÎČ, mitigating the process of fibrogenesis 13,40,41 .…”
Section: Discussionmentioning
confidence: 99%